2016
DOI: 10.1097/scs.0000000000002725
|View full text |Cite
|
Sign up to set email alerts
|

Management of Craniosynostosis at an Advanced Age

Abstract: Children who present in a delayed fashion with unrepaired craniosynostosis have high rates of debilitating headaches, developmental delays, head shape anomalies, and Chiari malformation. Five patients reporting preoperative headaches noted subjective improvements in headaches following delayed operation. Cranial reconstruction can be safely performed at an older age and is appropriate to consider in carefully selected patients for aesthetic and/or functional concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Additionally, the present study also investigated the role of patient age in the appropriateness of CT scan use in the diagnosis of craniosynostosis and found that older patient age significantly decreased the odds of operative intervention after CT scan by 70.0% if ordered by a craniofacial surgeon, while patient age did not significantly affect the likelihood of operative intervention after CT scan if ordered by a neurosurgeon or pediatrician. This finding could perhaps be explained by a decrease in judicious use of CT scanning in older pediatric patients seen by craniofacial surgeons due to an increased concern for possible significant co-existing abnormalities that could result from unaddressed craniosynostosis, but that do not necessarily require operative intervention 24 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the present study also investigated the role of patient age in the appropriateness of CT scan use in the diagnosis of craniosynostosis and found that older patient age significantly decreased the odds of operative intervention after CT scan by 70.0% if ordered by a craniofacial surgeon, while patient age did not significantly affect the likelihood of operative intervention after CT scan if ordered by a neurosurgeon or pediatrician. This finding could perhaps be explained by a decrease in judicious use of CT scanning in older pediatric patients seen by craniofacial surgeons due to an increased concern for possible significant co-existing abnormalities that could result from unaddressed craniosynostosis, but that do not necessarily require operative intervention 24 …”
Section: Discussionmentioning
confidence: 99%
“…Delayed craniosynostosis treatment is poorly described in the literature, but studies estimate that 11% to 51% 7–9 of craniosynostosis patients present to an appropriate craniofacial provider after 12 months of age. Small-sample studies indicate that this cohort can greatly benefit from surgical intervention even at an advanced age, showing improvements in developmental delays as well as reduction of debilitating headaches, intracranial pressure elevations, and other morbidities associated with uncorrected synostosis 5,10 . Although these results are encouraging, operative benefits are attenuated in this cohort compared with those who receive standard care.…”
mentioning
confidence: 86%
“…Although debate exists regarding the optimal operative window for craniosynostosis repair, the current standard of care for these patients involves calvarial remodeling before 1 year of age 1–4 . Uncorrected craniosynostosis past this age carries increased risk of brain growth restriction and elevated intracranial pressure, with sequelae ranging from headaches to developmental delays and functional/sensory impairments 5 . Moreover, older patients generally require more extensive operations and have increased rates of residual skull defects 6 .…”
mentioning
confidence: 99%
See 2 more Smart Citations